Solar Variability and Automated Analysis for Space Weather - Giersch, Owen David (Curtin University, 2016)
This thesis explores solar variability and particularly the consistency and accuracy of its measurement over the period 1945-2015. Automated algorithms have been implemented to measure to measure sunspot number, area and classification and compared with manual reduction techniques. Parameters developed were then used to determine X-ray associations with regions. Automated Ha flare analysis was also developed.